Case Report: A 31-year-old Post Cesarean Section Women with Intrahepatic Cholestasis of Pregnancy and Post Partum Bell’s Palsy - Syifa Mustika; RC Tarigan (The Indonesian Society for Digestive Endoscopy, 2018)
Intrahepatic cholestasis of pregnancy (ICP) is cholestasis condition characterized by pruritus, elevated serum aminotransferase and bile acid levels with onset in the second or third trimester of pregnancy. Estimated of ICP prevalence only 0.001% to 0.3%. Bell's Palsy is a neurological disorder that causes facial muscles on one side of the face to suddenly weaken or become paralyzed. Bell's Palsy is more common in young adults, older people, diabetics and pregnant women. A 31-year-old women with major complaint is yellow eyes. She got itching in all over the body. Patient was in second pregnancy with gestational age was 39-40 weeks. She suffered from unable to close her eyelid or blink. Patient was diagnosed with cholestasis intrahepatal in pregnancy and Bell’s palsy post partum. Diagnosis was established concluded from anamnesis, physical examination and hepar biopsy. The result of a liver biopsy showed intrahepatic cholestasis. From Fibroscan examination was visible with F2 category or Moderate Fibrosis. The main management of this patient is cesarean section with UDCA and corticosteroid therapy. Patient was administrated with antiviral therapy for her Bell’s Palsy condition. After 1 week hospitalization, patient was discharged with improvement of her major complaint.